Real Native Genius : How an Ex-Slave and a White Mormon Became Famous Indians - Hudson, Angela Pulley (Book collections on Project MUSE., 2015)
"Uniting disparate histories of slavery, Mormonism, popular culture, and American medicine, Angela Pulley Hudson weaves together a fascinating tale of ingenuity, imposture, and identity. While laying bare the complex relationship between race, religion, and gender across much of the nineteenth-century United States and Canada, Hudson shows how shifting concepts of identity were understood and performed in the context of vast social changes. Through the lives of Tubbee and Ceil, Hudson details the complex and fluid nature of Native identity during the antebellum period in the United States"--